Attitudes and practices of nurses toward oral care of hospitalized patients - A cross-sectional survey in Riyadh, Saudi Arabia - Deyaaldeen Mohammad Al Rababah; Mohammad Zakaria Nassani; Omar Ghazi Baker; Eyad M Alhelih; Suzan Ali Almomani; Samer Rastam (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Oral care of hospitalized patients is an important measure that aims to maintain and promote the health of oral and dental tissues. This study aimed to investigate nurses' attitudes and practices regarding oral care of hospitalized patients in Riyadh, Saudi Arabia. MATERIALS AND METHODS: A cross-sectional, descriptive design was implemented. The research instrument was a self-administered questionnaire that was designed and distributed among 300 nurses working at five hospitals located in Riyadh. RESULTS: Totally, 226 questionnaires were completed (response rate: 75%). Almost all participants (97.8%) think that providing oral hygiene is an important element of patient care and 90.7% think that nurses need to update their oral care knowledge and skills. Only 46% of the nurses reported the presence of a policy for oral care at their hospital unit and 55.3% indicated that patients are assessed for oral health at their department. About 56.2% of participants did not receive training on oral assessment and provision of oral care and a few nurses (2%) received training on oral care at their current job place. A large proportion of nurses (44%) expressed a desire to undergo training on oral care of hospitalized patients. Gender, nationality, and previous training were the most important predicators of a positive attitude. CONCLUSIONS: The outcome of this study indicates a positive attitude among the surveyed nurses toward provision of oral care for hospitalized patients. Current oral care practice in Saudi hospitals is suboptimal. Saudi hospitals need to pay more efforts to train their nursing staff and issue clear policies and guidelines regarding oral care of hospitalized patients.